VARRO, DICAEARCHUS, AND THE HISTORY OF ROMAN RES RUSTICAE. (12th December 2017) - NELSESTUEN, GRANT A.
Abstract: This article reconstructs the historical narrative underlying the account of Roman farming in De re rustica, thereby shedding new light on Varro's intellectual engagements in composing his agricultural treatise and methodology as a scholar of Rome. Central to this account is Dicaearchus of Messana's three-stage theory of human development, which not only provides an anthropological pedigree for agriculture (in book 1) and animal husbandry (in book 2), but also establishes the theoretical framework for Varro's innovative treatment of so-called 'animal husbandry of the villa' (in book 3). By presenting this last sphere of rustic production as a newly viable mode of farming contingent on the vast wealth and decline of morality in contemporary Rome, Varro uses it to emblematize 'urban life' as a fourth stage of human existence. The history of Roman farming thus offers a profoundly ambivalent narrative, entailing technological and material progress at the cost of moral decline.